2011
DOI: 10.3168/jds.2010-3371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differential supplementation of fatty acids during the peripartum and breeding periods of Holstein cows: II. Neutrophil fatty acids and function, and acute phase proteins

Abstract: The objectives were to evaluate the effects of differential supplementation of Ca salts (CS) of fatty acids (FA) on plasma acute phase proteins and both FA composition and function (i.e., activity and cytokine production) of neutrophils, during the peripartum and breeding periods. Holstein cows were assigned randomly to receive either CS of palm (PO) or safflower (SO) oils from 30 d prepartum until 35 d postpartum (dpp) and CS of PO or fish oil (FO) from 35 to 160 dpp. Supplementation of CS of FA was at 1.5% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 49 publications
2
58
1
18
Order By: Relevance
“…Of particular note, the haptoglobin concentrations in the cows with high milk SCC were significantly higher than those in plasma of the healthy cows (Eckersall et al, 2001;Pyö rä lä , 2003). These results are consistent with previous findings that transition cows supplemented with Ca salts of safflower oil had greater plasma haptoglobin concentrations than cows supplemented with Ca salts of palm oil (Silvestre et al, 2011). Dietary supplementation with polyunsaturated fatty acids has immunosuppressive effects through antigen presentation, T cell responses and fatty acid-derived inflammatory mediator production (Shaikh and Edidin, 2007;Yaqoob and Calder, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Of particular note, the haptoglobin concentrations in the cows with high milk SCC were significantly higher than those in plasma of the healthy cows (Eckersall et al, 2001;Pyö rä lä , 2003). These results are consistent with previous findings that transition cows supplemented with Ca salts of safflower oil had greater plasma haptoglobin concentrations than cows supplemented with Ca salts of palm oil (Silvestre et al, 2011). Dietary supplementation with polyunsaturated fatty acids has immunosuppressive effects through antigen presentation, T cell responses and fatty acid-derived inflammatory mediator production (Shaikh and Edidin, 2007;Yaqoob and Calder, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Ordóňez et al (2008) compared PHA and PHI of neutrophils from milk and blood using Staphylococcus aureus; those results are similar to the one in our C group. PHA and PHI were significantly lower (P < 0.05) in the LS group which is not in relation with Silvestre et al (2011). They used S. aureus and Escherichia coli to determine PHA of dairy cow neutrophils according to a different dietary fatty acid composition and found that dietary treatment did not influence PHA whereas bacteria species did.…”
Section: Discussionmentioning
confidence: 99%
“…Although unsaturated FA are known as modifiers of physiology and metabolism, for example, modulating immune function and reproduction in dairy cows (Silvestre et al, 2011a and2011b), they alter bacterial cell integrity (Maia et al, 2007) and impair ruminal fermentation. The matrix complex that surrounds the cotyledon(s) (which represents 90% of the weight and contains practically all the oil and protein) of oilseeds offers some protection to the access of ruminal microorganisms (Lock and Bauman, 2004), and can be added in lactating cow diets without decreasing NDF total tract digestion and impairing ruminal fermentation (Almeida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%